ISOLASI JAMUR Oncobasidium theobromae P.H.B TALBOT & KEANE PENYEBAB PENYAKIT VASCULAR STREAK DIEBACK PADA TANAMAN KAKAO DI LABORATORIUM - Nugraha Pratama Dhana; Lahmuddin Lubis; Lisnawita Lisnawita (Universitas Sumatera Utara, 2013)
Isolation of fungi Oncobasidium theobromae P.H.B Talbot and Keane cause disease VascularStreak Dieback (VSD) on cocoa plants in the laboratory. The research aims to isolateO. theobromae cause Vascular Streak Dieback (VSD) disease on cocoa in the Laboratory. Theresearch was conducted at the Laboratory of Plant Desease Faculty of Agriculture, University ofSumatra Utara.. The research results showed that O. theobromae has a mycelium shaped like cottonand thick white cream, thin walled hyphae, hyaline, with irregular septa, spores an oval with oneflat side, 10-15μm in length and width of 8-10μm.Keywords: Vascular Streak Dieback, Oncobasidium theobromae, cocoa